Seabird predation by great skuas Stercorarius skua - intra-specific competition for food? - Votier, S.C.; Bearhop, S.; Crane, J.E.; Manuel Arcos, J.; Furness, R.W. (Journal of Avian Biology, 2007)
Competition for food is widely cited as an important cost of coloniality among birds and much of the evidence in support of this hypothesis comes from studies of colonial piscivorous seabirds. However, for generalist seabirds able to switch between different prey types, the role of food availability in relation to colony size is unclear. Here we investigate patterns of the consumption of seabird prey in relation to colony size in a generalist seabird, the great skua Stercorarius skua , in Shetland, UK. At the population level skuas feed mainly on sandeels Ammodytes marinus and fishery discards, but respond to declines in fish availability to facultatively prey on other seabirds. By comparing the consumption of seabirds among seven different sized colonies, including one colony with artificially reduced numbers of skuas (Fair Isle), we investigate whether consumption of seabird prey is influenced by skua population size, while simultaneously measuring seabird prey availability. Data from five years also enables us to investigate the influence of annual variation in environmental conditions on seabird consumption. Using measures of body condition and reproductive performance we investigate the consequences of living in different sized colonies, which may provide insight into ultimate costs of nesting at high population density. Skua diets varied among colonies and the proportion of seabird prey in the diet was inversely related to skua colony size, despite similar per capita numbers of seabirds across colonies. At the colony where their numbers were artificially suppressed, skuas consumed a greater proportion of seabirds per capita. Highly significant year effects in seabird predation were observed but the pattern among colonies remained consistent over time. Two measures of adult body condition (pectoral muscle index and mean corpuscular volume) revealed that adult great skuas were in poorer condition at the largest colony (Foula), but reproductive performance did not alter significantly among colonies. This ...